Vaccine and Therapeutic Options To Control Chikungunya Virus - Powers, Ann M. (Clin Microbiol Rev, 2017)
Beginning in 2004, chikungunya virus (CHIKV) went from an endemic pathogen limited to Africa and Asia that caused periodic outbreaks to a global pathogen. Given that outbreaks caused by CHIKV have continued and expanded, serious consideration must be given to identifying potential options for vaccines and therapeutics. Currently, there are no licensed products in this realm, and control relies completely on the use of personal protective measures and integrated vector control, which are only minimally effective. Therefore, it is prudent to urgently examine further possibilities for control. Vaccines have been shown to be highly effective against vector-borne diseases. However, as CHIKV is known to rapidly spread and generate high attack rates, therapeutics would also be highly valuable. Several candidates are currently being developed; this review describes the multiple options under consideration for future development and assesses their relative advantages and disadvantages.